Beyond Fields and Families: Unraveling Socio-demographic Threads in CSA Engagement of Indonesian Market - Rahmatika, Maula Fadhilata; Suman, Agus; Syafitri, Wildan; Muljaningsih, Sri (Journal of Ecohumanism, 2024)
Community Supported Agriculture (CSA) promotes sustainable farming through direct producer-consumer relationships but remains underutilized in Indonesia. This study examines socio-demographic factors influencing CSA participation among 385 Indonesian non-participants and emphasizes communication's role in overcoming engagement barriers. Findings reveal urban residents and larger households are more likely to join CSA due to better information access and convenience. Income has a near-significant impact, while education shows no effect, highlighting awareness gaps. Strategic communication campaigns targeting urban areas, affordable memberships for low-income groups, and educational initiatives can increase CSA participation. Policymakers should integrate CSA into urban planning, leveraging communication to address risk perceptions and build trust. Future research should explore cultural attitudes and digital platforms' influence to strengthen Indonesia’s sustainable agriculture.